2021
DOI: 10.1097/pas.0000000000001826
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2SC, AKR1B10, and FH Antibodies as Potential Biomarkers for FH-deficient Uterine Leiomyomas

Abstract: Hereditary leiomyomatosis and renal cell cancer (HLRCC) is a tumor predisposition syndrome caused by germline fumarate hydratase (FH) mutations and characterized by uterine and cutaneous leiomyomas and renal cell cancer. Currently, there is no generally approved method to differentiate FH-deficient uterine leiomyomas from other leiomyomas. Here, we analyzed 3 antibodies (S-(2-succino)-cysteine [2SC], aldo-keto reductase family 1, member B10 [AKR1B10], and FH) as potential biomarkers. The study consisted of 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Aldo-Keto Reductase Family 1 Member B10 (AKR1B10), an NADPH-dependent reductase that catalyzes the reduction of a wide variety of carbonyl-containing compounds, is often overexpressed in FH deficient tumors, including LM [4]. A recent study showed that AKR1B10 can be a specific and sensitive marker of FH-LM [24]. Our IHC assay confirmed the previous report and detected a high expression of AKR1B10 only in FH-LM but not in other LM subtypes (Fig 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Aldo-Keto Reductase Family 1 Member B10 (AKR1B10), an NADPH-dependent reductase that catalyzes the reduction of a wide variety of carbonyl-containing compounds, is often overexpressed in FH deficient tumors, including LM [4]. A recent study showed that AKR1B10 can be a specific and sensitive marker of FH-LM [24]. Our IHC assay confirmed the previous report and detected a high expression of AKR1B10 only in FH-LM but not in other LM subtypes (Fig 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we recently analyzed publicly available leiomyoma data and reclassified two leiomyomas as FH-deficient partly based on the expression of AKR1B10 [ 16 ]. Using FH-deficient tumors derived from HLRCC patients and sporadic leiomyomas with biallelic loss of FH , we recently showed that AKR1B10 immunohistochemistry can act as a biomarker on protein-level as well [ 17 ]. In this study, we present a novel uterine leiomyoma subtype that is FH-proficient but displays AKR1B10 protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Although these morphologic features prove to be relevant for the detection of HLRCC, 2 immunohistochemical stains, 2-succinocysteine (2SC), and FH can be applicable to identify FH deficiency. 22,23 In this study, the relationship between the characteristic morphologic findings of leiomyomas thought to be FH-deficient and the expression of FH and 2SC immunohistochemistry (IHC), and the frequency of FH and 2SC IHC expression in uterine leiomyomas detected in young patients are aimed to be scrutinized. a database search at the Pathology Department of Istanbul Medical Faculty during the period of 2018 to 2022.…”
mentioning
confidence: 99%